Spatial Heterogeneity and Co-occurrence of Mucosal and Luminal Microbiome across Swine Intestinal Tract - Zhang, Li; Wu, Weida; Lee, Yuan-Kun; Xie, Jingjing; Zhang, Hongfu (Frontiers in Microbiology, 2018)
Pigs are one of the most important economic livestock. Gut microbiota is not only critical to the health but also the production efficiency of pigs. Manipulating gut microbiota relies on the full view of gut microbiome and the understanding of drive forces shaping microbial communities. 16s rDNA sequencing was used to profile microbiota along the longitudinal and radical axes to obtain the topographical map of microbiome in different intestinal compartments in young pigs. Alpha and beta-diversities revealed distinct differences in microbial compositions between the distal ileum and cecum and colon, as well as between the lumen and mucosa. Firmicutes and Proteobacteria dominated in the ileum, constituting 95% and 80% of the luminal and mucosa-attached microbiome. Transitioning from the small intestine to the large intestine, luminal Bacteroidetes increased from 1.69% to 45.98% in the cecum and 40.09% in the colon, while mucosal Bacteroidetes raised from 9% to 35.36% and 27.96%. Concurrently, luminal Firmicutes and Proteobacteria and mucosal-attached Proteobacteria remarkably decreased. By co-occurrence network analyses, Prevotellaceae, Ruminococcaceae, Lachnospiraceae and Veillonellaceae were recognized as the central nodes of luminal microbial network, and Prevotellaceae and Enterobacteriaceae, Caulobacteraceae, Enterococcaceae, Xanthomonadaceae, Pseudomonadaceae were identified as mucosal central nodes. Co-abundance was uncovered among Prevotellaceae, Lachnospiraceae and Veillonellaceae in the luminal and mucosal microbiome, while opportunistic pathogens from γ-Proteobacteria in the mucosa. Strong co-exclusion was shown between Enterobacteriaceae with Prevotellaceae-centered microbial groups in the lumen. Redundancy analysis found bile acids and short chain fatty acids explained 37.1% and 41% of variations in the luminal microbial composition, respectively. Primary bile acid, taurine- and glycine- conjugated bile acids were positively correlated with Lactobacillaceae, Enterobacteriaceae, Clostridiaceae_1, Peptostreptococcaceae, whereas secondary bile acids, acetate, propionate, butyrate and valerate were positively correlated with Prevotellaceae, Acidaminococcaceae, Ruminococcaceae, Lachnospiraceae, Desulfovibronaceae, Veillonellaceae. Functional analyses demonstrated that Prevotella, Veillonellaceae, Lachnospiraceae and Ruminococcaceae were positively correlated with gene functions related to amino acids, energy, cofactors and vitamins metabolism, which are indispensable for the hosts. These results suggested site specific colonization and co-occurrence of swine gut microbiome closely relate to the microenvironment in each niche. Interactions of core gut microbiome greatly contributed to metabolism and/or immunity in the swine intestine.